2018
DOI: 10.5430/ijfr.v10n1p86
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Audit Quality on Earnings Quality: Evidence From Indonesia Stock Exchange

Abstract: This research was conducted to test the effect of audit quality on earnings quality. Its observed data consisted of 116 annual data of manufacturing companies listed in the Indonesia Stock Exchange within 2011-2014. The proxies of audit quality are auditor size, audit tenure and audit specialization. The earnings quality was formed from the attributes of accrual quality, persistence, predictability, and income smoothing. The analysis techniques for this research involved (1) an confirmatory factor analysis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
6
1
1
Order By: Relevance
“…Additionally, the result demonstrates that the higher the AFT, the lower the EM processes. This is supported by the agency theory and is consistent with prior studies, such as Bauwhede et al (2003), Sumiadji and Subiyantoro (2009), Alsufy et al (2020) and Wijaya (2020). A possible explanation for this result is that the high audit firm turnover serves to promote audit independence, resulting in increased control levels and decreased EM practices in the client’s company.…”
Section: Data Analysis and Findingssupporting
confidence: 88%
See 3 more Smart Citations
“…Additionally, the result demonstrates that the higher the AFT, the lower the EM processes. This is supported by the agency theory and is consistent with prior studies, such as Bauwhede et al (2003), Sumiadji and Subiyantoro (2009), Alsufy et al (2020) and Wijaya (2020). A possible explanation for this result is that the high audit firm turnover serves to promote audit independence, resulting in increased control levels and decreased EM practices in the client’s company.…”
Section: Data Analysis and Findingssupporting
confidence: 88%
“…According to previous literature, the audit quality is measured by three main proxies, namely, size of audit firm (whether or not the company is audited by a big-firm auditor), industry specialization of audit firms (whether or not the company is audited by industry-specialist audit firm) and an audit tenure (the length of the audit firm–client relationship) (Abu Afifa et al , 2020; Al-Thuneibat et al , 2011; Sumiadji and Subiyantoro, 2009). Hence, this study also used these main proxies to measure the audit quality, where audit quality is included in the study model as an independent variable.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hegazy, Al Sabagh, & Hamdy (2015) concluded that a specialized auditor is associated with less earnings management than a non-specialist auditor, and there is a relationship between earnings management and the auditor's specialization. yes Sumiadji, Grahita, & Edi (2019) indicated a positive effect between the tenure of the auditor and earnings management. Auditor tenure has a significant relationship with earnings management and minimizes earnings manipulation (Ibrahim, Mansor, & Ahmad, 2020;Putra & FitoMela, 2019;Yasser & Soliman, 2018).…”
Section: Audit Quality and Earnings Managementmentioning
confidence: 99%